PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA AUDIOVISUAL TERHADAP DUKUNGAN SUAMI DALAM INISIASI MENYUSU DINI DI PUSKESMAS JETIS KOTA YOGYAKARTA - , EKA SETIAWATI PUTRI; , Wenny Artanty Nisman, S.Kep., Ns., M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Early initiation of breastfeeding (IMD) is the baby started breastfeeding immediately after birth for at least 1 hour first. One of the factors that influence the initiation of early breastfeeding is the husband. Partner support can be emotional support, informational, instrumental, and positive ratings. Husbands needs to obtain information about early initiation of breastfeeding in order to provide support in the initiation of breastfeeding. Objective: To determine the effect of health education with audiovisual media to partner support in the early initiation of breastfeeding Methods: This study used pre-experimental, one-group pretest-posttest design. The experiment was conducted in the Puskesmas Jetis in Yogyakarta on March until May 2014 with a sample of 20 husbands. Measurements using a questionnaire partner support. Data analysis using a paired t test. Results: The results showed the average value of the pretest and posttest partner support 83.40 and 86.06. Results of a paired t test against partner support showed a significant difference in the partner support before and after the administration of health education with audiovisual media (P <0.05). Conclusion: There is an influence of health education with audiovisual media to partner support in the early initiation of breastfeeding in Puskesmas Jetis Yogyakarta.